Expression of Th17/Treg related molecules in gastric cancer tissues - Meng, Xinying; Zhu, Shengtao; Dong, Quanjiang; Zhang, Shutian; Ma, Jian; Zhou, Changhong (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: The function of regulatory T cells (Treg) and helper T cells 17 (Th17) related indexes, such as interleukin (IL)-6, IL-17, transforming growth factor (TGF)-β1, and forkhead box protein 3(FoxP3) in gastric adenocarcinoma tissues remains undefined. We investigated and analyzed the relevance of the proteins with the clinicopathological characteristics and the interactions among them in gastric cancer. Materials and Methods: A total 68 gastric cancer patients and 40 healthy controls were enrolled. Immunohistochemistry (IHC) as well as quantitative real-time reverse transcription- polymerase chain reaction (RT-PCR) was used to determine the expression levels of IL-6, TGF-β1, IL-17, and FoxP3 in the prepared tissues. Statistical analysis included ANOVA and chi-square test. Results: The expression levels of IL-6, IL-17, FoxP3, and TGF-β1 had significantly increased in cancer tissues compared to controls. Clinical staging of gastric cancer were correlated with the rise of IL-6, IL-17, FoxP3, and TGF-β1 levels expressed in cancer tissues. The expression level of TGF-β1 and IL-6 was positively related to that of IL-17 and FoxP3, similar to FoxP3 and IL-17 in gastric cancer tissues. Conclusion: IL-6, TGF-β1, FoxP3, and IL-17 may promote the progression of gastric cancer individually or jointly and have complex interactions. Cite this article as: Meng X, Zhu S, Dong Q, Zhang S, Ma J, Zhou C. Expression of Th17/Treg related molecules in gastric cancer tissues. Turk J Gastroenterol 2018; 29: 44-9.